2006
DOI: 10.1074/jbc.m511367200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Integrin Activity by MIA

Abstract: MIA (melanoma inhibitory activity) has been identified as a small protein secreted from malignant melanoma cells, which interacts with extracellular matrix proteins including fibronectin. Here, we show that MIA negatively regulates the activity of the mitogen-activated protein kinase pathway in malignant melanoma. Using far Western blotting and co-immunoprecipitation we searched for MIA-binding cell surface proteins. We found that MIA interacts with integrin ␣4␤1 and ␣5␤1, leading to down-regulation of integri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 26 publications
3
62
1
Order By: Relevance
“…In line with this assumption, external addition of MIA protein does not support migration but results in unpolarized cell detachment and reduced invasiveness in Boyden chamber assays [2]. To account for the pro-migratory effect of endogenously expressed and secreted MIA protein, we proposed that MIA secretion is directed to the rear end of a migrating cell where it can bind to integrins and thereby promote cell retraction [7]. MIA-integrin complexes are subsequently internalized at the rear of the cell [8].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In line with this assumption, external addition of MIA protein does not support migration but results in unpolarized cell detachment and reduced invasiveness in Boyden chamber assays [2]. To account for the pro-migratory effect of endogenously expressed and secreted MIA protein, we proposed that MIA secretion is directed to the rear end of a migrating cell where it can bind to integrins and thereby promote cell retraction [7]. MIA-integrin complexes are subsequently internalized at the rear of the cell [8].…”
Section: Introductionmentioning
confidence: 78%
“…MIA protein was described to directly interact with cell adhesion receptors, integrin α 4 β 1 and integrin α 5 β 1 [7], as well as with extracellular matrix molecules including fibronectin, tenascin and laminin [2]. As a result, matrix structures surrounding the cell and integrin adhesion molecules are masked by MIA protein, which consequently impacts melanoma cell attachment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies using far Western blotting and co-immunoprecipitation MIA protein was identified to bind to the cell surface proteins integrin a 4 b 1 and integrin a 5 b 1 . 12 Thus, MIA protein modulates integrin activity and thereby mediates detachment of cells from extracellular matrix proteins, resulting in enhanced invasive and migratory potential of melanoma cells.…”
mentioning
confidence: 99%